Dynamics of City Life: Elements of Cosmopolitanism in Khaled Husseini’s The Kite Runner - Dhakal, Sibu (NPRC Journal of Multidisciplinary Research, 2025)
Background: Khaled Hosseini’s debut novel, The Kite Runner (2003) reflects the shifting dynamics of city life in Kabul. It presents a narrative of friendship, betrayal, redemption, war, and migration in the backdrop of Kabul. It also explores the complexities of city life and reflects how it is affected by Afghanistan’s politics, history, and culture, portraying Kabul before and after the Taliban insurgency. Methods: This study examines the shifting dynamics of city life in Kabul from a cosmopolitan perspective. This research explores the ethnic and sectarian violence in Afghanistan and showcases its impact on the cosmopolitan elements of Kabul city. Result: This research reveals that Kabul had a peaceful life and cosmopolitan character before the outbreak of violence; however, the city gradually lost its cosmopolitanism due to the armed conflict that followed. Conclusion: The multiple dynamics of Kabul City are primarily affected by the war, and the elements of cosmopolitanism reveal a fluctuating nature. Novelty: This research presents a novel perspective on the shifting dynamics of city life in Kabul, providing insight into the cosmopolitan elements and their fluctuating nature.